The Seeds of Tomorrow : Investigating Adolescent Perception of the Future with the Futures Consciousness Scale for Adolescents - Lalot, Fanny; Ahvenharju, Sanna; Bishop, Peter C. (Elsevier, 2025)
Futures Consciousness (FC) describes the human capacity to understand, anticipate, prepare for and embrace the future. Differences in FC between individuals (as a psychological construct) can be reliably measured quantitatively with the Futures Consciousness scale. However, the FC scale is only suitable for adult population. Based on the contention that Futures Consciousness emerges at a younger age, we endeavour to develop and validate an adapted version of the FC scale that is suitable for adolescents (aged 11-18). This paper presents the statistical analyses that led to the validation of a 15-item instrument, the FC-Adolescent scale. Data from N = 1138 adolescents from five countries allowed us to validate the scale in four languages (English, Dutch, Italian, and Turkish) through a dual approach of confirmatory factor analyses and ant colony optimisation item-sampling procedure. The results show that the five-dimensional structure of FC also holds for adolescents and that it can be measured with the scale developed here. Interestingly, we found no correlation between FC and age in the range of 11-18 years old. We discuss implications for research and potential applications for educators and foresight practitioners.